Kecerdasan Spiritual Melalui Kegiatan Shalat Berjamaah Dhuha dan Fardhu pada Siswa Kelas IV di SDIT Muhammadiyah Al-Kautsar - Parwati, Ratih; , Honest Ummi Kaltsum, S.S., M.Hum (2017)
This study aims to (1) describe the spiritual intelligence through prayers Duha, and obligatory in grade IV in SDIT Muhammadiyah Al-Kauthar, (2) describe the barriers to spiritual intelligence through prayers Duha, and obligatory in grade IV in SDIT Muhammadiyah Al -Kautsar, (3) describe the solution of barriers to spiritual intelligence through fard prayers Duha and fourth grade students at Al-Kautsar SDIT Muhammadiyah. This study is a qualitative research with phenomenological research type. Data collection techniques in this research is observation, interview, and documentation. The validity of research data using triangulation and triangulation techniques. This research data analysis techniques using interactive analysis techniques include data reduction, data display, and conclusion. The results showed that (1) the fourth grade students have spiritual intelligence, namely (a) the students have an attitude that is sociable and active, (b) the students have a level of self-awareness is high, (c) the student has the ability to deal with the problem, (d) students have a quality of life which is based on positive values, (e) the students have an aversion to cause harm to others, (f) fourth grade students often ask "why" or "what if?" to teachers and parents. (2) barriers to spiritual intelligence through Duha and fard prayers in grade IV, among others: (a) the guidance of teachers in schools is not followed by the parents when at home, (b) some students do not read prayers and hadith before implementing Duha and fard prayers. (3) the solution of barriers barriers spiritual intelligence through Duha and fard prayers in grade IV, among others: (a) the teacher held a meeting with the parents of students organized by the school, (b) the teacher approached the student and then go read a prayer or hadith that is being read.